Collateral Reuse and Balance Sheet Space - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2017)
Transactions on wholesale capital markets are often secured by marketable collateral. However, collateral needs balance sheet space to move within the financial system. Certain new regulations that constrain private sector bank balance sheets may have the effect of impeding collateral flows. This may have important consequences for monetary policy transmission, for short term money market functioning, and for market liquidity. In this context (and in contrast to the literature, which has focused mainly on the repo market), this paper analyzes securities-lending, derivatives, and prime-brokerage markets as suppliers of collateral. It highlights the incentives created by new regulations for different suppliers of collateral. Moreover, it argues that the central banks should be mindful of the effect of their actions on the ability of markets to intermediate collateral.